Hubungan Perhatian Orang Tua dengan Motivasi dan Kesiapan Belajar Siswa Kelas V SDN 2 Surabaya Kec. Limbangan Kab. Garut - Abdul Hakim; Indriyanti Karmila (caXra: Jurnal Pendidikan Sekolah Dasar, 2022)
This study uses the correlational method to determine the relationship between parental attention and learning motivation and learning readiness of fifth grade students at SDN 2 Surabaya. Based on the results of the study showed that: (1) there is a relationship between parental attention and student learning motivation with a significance value for the effect of parental attention on motivation is 0.013 < 0.05 and for the tcount value is 2.681 > 2.055, (2) there is a relationship between people's attention parents with student learning readiness, this is evidenced by the significance value for the effect of parental attention on learning readiness is 0.000 < 0.05 and for the t count value is 4.684 > 2.055, (3) parental attention has an influence on learning motivation and student readiness to learn by see a percentage of 22.3% parental attention has an influence on student motivation. Meanwhile, 46.78% of parents' attention has an influence on the learning readiness of fifth grade students at SDN 2 Surabaya.